Writing for Strategic Communication Industries - Roberts, Jasmine (Open textbook library., 2016)
Good writing skills are important in today's competitive work environment. This is especially the case for communication-related professions such as public relations, brand communication, journalism, and marketing. Writing for Strategic Communication Industries emphasizes practical application of academic inquiry to help readers improve their writing skills. This book gives readers: Straightforward chapters that use real-world examples to illustrate key points. Discussion of different writing styles and techniques. Examples of communication materials such as press releases, creative briefs, feature articles, and more. Embedded videos of insights from communication professionals. Tips on pitching to the media. A collection of popular sources for further explanation.